2004
DOI: 10.1002/cbdv.200490138
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Terpenoids and Guggulusteroids from Commiphora mukul Gum Resin of Potential Anti‐Inflammatory Interest

Abstract: Guggulu, the gum resin from Commiphora mukul, is one of the components of various formulations of traditional Ayurvedic medicine to treat inflammation, obesity, and lipid disorders. In most preparations of Ayurvedic medicine in India, guggulu is boiled prior to its use. Therefore, guggulu was boiled with H2O prior to extractions in our study. Bioassay-guided isolation of compounds from the hexane-soluble portion of the MeOH extract of guggulu yielded cembrenoids, 1-6, a bicyclic diterpene, 7, guggulusterone de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 18 publications
2
46
0
1
Order By: Relevance
“…[8] Verticillol (#5) has been isolated from olibanum oil [9] and guggul. [10] Our NMR assignments are in general agreement with those reported previously except the 13 C assignments for methyl groups at position C18 and C20 for Cembrene A (#2), [8] and at C18 and C19 for mukulol (#4). [8] The discrepancy is attributed to the heteronuclear chemical shift correlation methods used in this report, which provide accurate information on the correlation between 1 H and 13 C and were not available to the earlier reports.…”
Section: Resultssupporting
confidence: 92%
“…[8] Verticillol (#5) has been isolated from olibanum oil [9] and guggul. [10] Our NMR assignments are in general agreement with those reported previously except the 13 C assignments for methyl groups at position C18 and C20 for Cembrene A (#2), [8] and at C18 and C19 for mukulol (#4). [8] The discrepancy is attributed to the heteronuclear chemical shift correlation methods used in this report, which provide accurate information on the correlation between 1 H and 13 C and were not available to the earlier reports.…”
Section: Resultssupporting
confidence: 92%
“…It was reported that Zguggulsterone, E-guggulsterone, myrrhanone A, and myrrhanol A inhibited nitric oxide production in lipopolysaccharide-activated mouse peritoneal macrophages (Matsuda et al, 2004). Moreover, E-guggulsterone possessed the cyclooxygenase (COX) enzyme inhibitory activities (Francis et al, 2004). In this present study, seven major constituents including three sesquiterpenes, one diterpene and three diterpenic acids were identified by UPLC-MS/MS from the analgesic and anti-inflammatory fraction.…”
Section: Peaksmentioning
confidence: 90%
“…Myrrhanol A (23) and mukulol (25) inhibited the induction of inducible nitric oxide synthase (iNOS) in LPS-activated mouse peritoneal macrophages (Matsuda et al, 2004a). Concerning the COX inhibitory effect, cembrene (26) and E-guggulsterone (22) are most active, with 79% and 67% inhibition against COX-1, and with 83% and 54% inhibition against COX-2 at 100 ppm (Francis et al, 2004).…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%